2019
DOI: 10.1080/02656736.2018.1528392
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation of hyperplastic parathyroid glands is a treatment option for end-stage renal disease patients ineligible for surgical resection

Abstract: An Yu (2019) Microwave ablation of hyperplastic parathyroid glands is a treatment option for end-stage renal disease patients ineligible for surgical resection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…The studies covered a period !8 years, from 2009 to 2017. Two were retrospective cohort studies [26,27], and six were retrospective self-control studies [28][29][30][31][32][33]. The mean follow-up period ranged from six to 23 months, and the sample size ranged from 9-56 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies covered a period !8 years, from 2009 to 2017. Two were retrospective cohort studies [26,27], and six were retrospective self-control studies [28][29][30][31][32][33]. The mean follow-up period ranged from six to 23 months, and the sample size ranged from 9-56 patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main reasons for this result. First, analysis of the eight included studies showed that many patients were not eligible for surgical resection of a recurrence after primary surgery [28,31,33]. These cases are more difficult to perform, so the incidence of complications may be higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parathyroidectomy (PTX) is necessary for SHPT patients who are refractory to medical therapy . Recently, due to minimal injury, an effective decrease in intact parathyroid hormone (iPTH) and good repeatability, ultrasound (US)‐guided percutaneous microwave ablation (MWA) has been gradually accepted in clinical practice …”
Section: Introductionmentioning
confidence: 99%